Motion Influences the Perception of Background Lightness. (February 2014) - Ashida, Hiroshi; Scott-Samuel, Nicholas E.
Uniform backgrounds appear lighter or darker when elements containing luminance gradients move across them, a phenomenon first presented by Ko Nakamura at the 2010 Illusion Contest in Japan. We measured the apparent lightness of the background with a configuration where the grey background was overlaid with moving square patches of vertically oriented luminance gradient. For black-to-grey gradients, the background appeared lighter when the black edges were leading than when they were trailing. For white-to-grey gradients, the background appeared darker when the white edges were leading than when they were trailing. For white-to-black gradients, the background appeared darker with a white edge leading and lighter with a dark edge leading, but the effects were weaker. These results demonstrate that lightness contrast can be modulated by the direction of motion of the inducing patterns. The smooth gradient is essential, because the effect disappeared when the black-to-white gradient was replaced with the binary black and white pattern. We speculate that asymmetry in the processing of a temporal gradient with increasing and decreasing contrast, as proposed to explain the "Rotating Snakes" illusion (Murakami, Kitaoka, & Ashida, 2006, Vision Research, 46, 2421–2431), might be the basis for this effect.